Let's denote the total amount of Robux you earned as \( R \) and the cost of the Golden Microphone as \( C \).
-
Equation for remaining Robux after purchase:
\[ R - C = \text{Remaining Robux} \] Substituting the values, we have:
\[ 146 - 70 = \text{Remaining Robux} \]
Thus, the equation is:
\[ 146 - 70 = R' \]
where \( R' \) is the remaining Robux.
-
Equation using inverse operation to check the answer:
To check your answer, you can use the inverse operation by adding the cost of the Golden Microphone back to the remaining Robux and comparing it to the total amount of Robux you started with:
\[ R' + C = R \]
Substituting the values we found:
\[ R' + 70 = 146 \]
Now solve for \( R' \):
\[ R' = 146 - 70 \]
So summarizing:
-
Remaining Robux equation: \[ 146 - 70 = R' \]
-
Check with inverse operation: \[ R' + 70 = 146 \]